As prisões de São Paulo: dinâmicas, fluxos e as implicações nas trajetórias de egressos prisionais. Uma perspectiva a partir do monitor preso de educação - Melo, Felipe Athayde Lins de (2012)
The striking phenomenon of growing urban violence and the expansion of the prison while a privileged mode of punishment in contemporary societies have increasingly attracted the attention of researchers for the description and analysis of the processes that take place in prison and from it. This research is part of in this field, having a concern to question a binomial normative of the prison policy, whereby the experience in prisons opposes the paths to "reintegration" and "criminal recidivism." Discussing these concepts and opposing to them, the research points to the need to understand the social dynamics that make up the life of prison former inmates, intersecting them with the practices of the prison administration and with the flow and the increasingly more frequent links between the inside and the outside of prisons. Thus, I seek to understand the social processes that mark the paths of former inmates of São Paulo s prison system, subject little explored in the Brazilian literature and whose approach dialogues with recent studies on the social dynamics which have an effect on the lives in prison. It also dialogues with studies that are not focused on the prison, but whose themes this institution presents itself, whether as a differentiation marker of individuals, whether as a dissemination beam of social relations linked to the world of crime. The study takes place around the description of the trajectory of Diego s life, former inmate of São Paulo s prison system, and his interaction, at different times, with the research author. Therefore, São Paulo s prison system own dynamics are described and unofficial processes of shared management of prisons are emphasized between the state administration and the different groups of prisoners currently existing. In this sharing, the education inmate monitor stands out, highlighted position occupied by Diego.